DIGITAL MULTIMODAL COMPOSING IN EFL PRE-SERVICE TEACHERS’ SLIDES: A SYSTEMIC FUNCTIONAL MULTIMODAL DISCOURSE ANALYSIS - Lola, Viville Irena; Emilia, Emi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Presentation slides are highly incorporated in the classroom. However, the EFL pre-service teachers’ ability to compose meaning across different modes in presentation slides remains underexplored. This study investigates how a group of four EFL pre-service teachers designed presentation slides by analysing the visual, verbal, and gestural modes through the lens of Systemic Functional Multimodal Discourse Analysis (SF-MDA). The research aims to examine how ideational, interpersonal, and textual meanings are realised in the multimodal artefacts, students’ design rationale, and how the three modes unite to achieve pedagogical goals, i.e. intersemiosis. The data included 15 presentation slides and an interview transcript, which provided insight into the EFL pre-service teachers’ design rationale. Findings indicate that although the slides employed the three modes, the analysis found limited intersemiosis, with modes, particularly the visual mode, not co-constructing meaning. This reflects a gap between the designers’ intention to engage students and the actual execution. The study concludes that pre-service teachers require not only theoretical exposure to multimodality but also structured practice in designing materials where meaning is distributed meaningfully across modes. These findings highlight the need for teacher education to develop curriculum that explicitly scaffolds digital multimodal composing skills.